Essential oil with mosquito-repellent potential from plectranthus amboinicus leaves against aedes aegypti via human volunteer study - Rizafizah Othaman,; Sumathy Raghavan,; Rozida Mohd Khalid,; Nabhan Sharer,; Muntaz Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Plectranthus amboinicus (PA) is a highly aromatic perennial shrub that belongs to the Lamiaceae family. It has thick, f leshy and succulent leaves and stem. The margins of the leaves contain numerous glandular hairs that produce essential oil. The essential oil of PA(PAEO) exhibits therapeutical, nutritional, antioxidant, antimicrobial, insecticidal, and insect repellent potentials. The objective of this study was to evaluate and compare the repellent properties of PAEO and DEET against Aedes aegypti mosquitoes, which are known carriers of dengue fever. The extraction of PAEO was carried out using hydrodistillation method while the chemical profile was analysed by gas chromatography-mass spectrometry (GC-MS) technique. The bioefficacy test was conducted according to the household insecticide products personal mosquito repellent evaluation method for biological efficacy (First revision) (MS1497:2007) provided by the Standard and Industrial Research Institute of Malaysia (SIRIM) with slight modification. 10% PAEO was used as test solution while 10% DEET was used as positive control. Fabric and patches treated with 10% PAEO were tested on human volunteers. Both the fabric and the patch, treated with 10% PAEO, exhibit excellent repellency (97 - 100%) against Ae. aegypti mosquitoes for a duration of up to 240 min (4 h) post-application. In contrast, 10% DEET, which initially showed a comparable repellency (99%) 30 min after application, experiences a gradual decline in repellency over time, reaching a 51% repellency rate at the end of the test (240 min post-application). A two-way ANOVA analysis indicates significant effect for type of treatment (p = 0.016) but with no significant difference between the exposure time. Tukey’s test showed significant differences between 10% PAEO-treated patches and 10% DEET (p = 0.016), and between 10% PAEO-treated fabric and 10% DEET (p = 0.026). These findings suggest that PAEO is potentially an effective natural repellent against Ae. aegypti.